PLA2G6 mutations associated with a continuous clinical spectrum from neuroaxonal dystrophy to hereditary spastic paraplegia. Issue 5 (19th April 2017) - Ozes, B.; Karagoz, N.; Schüle, R.; Rebelo, A.; Sobrido, M.‐J.; Harmuth, F.; Synofzik, M.; Pascual, S.I.P.; Colak, M.; Ciftci‐Kavaklioglu, B.; Kara, B.; Ordóñez‐Ugalde, A.; et al.
Abstract : PLA2G6‐associated neurodegeneration (PLAN) and hereditary spastic paraplegia (HSP) are 2 groups of heterogeneous neurodegenerative diseases. In this study, we report PLA2G6 gene mutations in 3 families from Turkey, Morocco, and Romania. Two affected Turkish siblings presenting HSP adds the disease to PLAN phenotypes. They were homozygous for the PLA2G6 missense c.2239C>T, p.Arg747Trp variant and the ages of onset were 9 and 21. Parkinsonism, dystonia or cognitive decline were not the clinical elements in these patients contrary to the cases that has been previously reported with the same variant, however, iron accumulation was evident in their cranial magnetic resonance imaging. The Moroccan patient was homozygous for a novel missense c.1786C>T, p.Leu596Phe variant and the Romanian patient had 2 novel mutations; c.1898C>T, p.Ala633Val and c.1765_1768del, p.Ser589ThrfsTer76. Both of these patients conformed better to childhood onset PLAN with the age of onset at 4 and 7 years, respectively. Interestingly, all identified mutations were affecting the highly conserved patatin‐like phospholipase domain of the PLA2G6 protein. Abstract : A, Brain iron accumulation in Turkish patients in association with HSP phenotype and PLA2G6 mutation, B, atrophy of cerebellum in Moroccan and C, Romanian patients with child onset PLAN.